Non‐cardiogenic pulmonary oedema and multisystemic haemorrhage secondary to an accidental intravenous injection of melarsomine in a dog. Issue 4 (29th September 2021) - Wolf, Johanna; Law, Jerry M.; Lynch, Alex
Abstract: An 8‐month‐old female entire Labradoodle was referred for further management of severe non‐cardiogenic pulmonary oedema after an accidental intravenous injection of the arsenical compound melarsomine. On arrival, the dog was non‐ambulatory, obtunded and in severe respiratory distress. Due to profound hypoxaemia despite oxygen supplementation, the dog was intubated and mechanically ventilated. While anaesthetised, the dog experienced three episodes of cardiac arrest with return of spontaneous circulation after cardiopulmonary resuscitation. However, due to continued severe hypoxaemia and haemodynamic instability, euthanasia was elected by the owners. On necropsy, marked pulmonary oedema and haemorrhage into multiple organs, including the endocardium and brain, were identified. Although no other reports describe the consequences of intravenous melarsomine in dogs, the postmortem findings are very similar to intravenous arsenic toxicity in humans. Furthermore, this case report highlights the importance of accurate drug labelling.